A ribonuclease-dependent cleavable beacon primer triggering DNA amplification for single nucleotide mutation detection with ultrahigh sensitivity and selectivity. Issue 84 (3rd October 2019) - Ding, Xiong; Yin, Kun; Chen, Ju; Wang, Kepeng; Liu, Changchun
Abstract : A ribonuclease-dependent cleavable beacon primer was developed to trigger DNA amplification for single nucleotide mutation detection with ultrahigh sensitivity and selectivity. Abstract : We described a ribonuclease-dependent cleavable beacon primer, an energy-transfer-tagged oligonucleotide inserted with a ribonucleotide, which can be cleaved by ribonuclease to generate enhanced fluorescence signals and initiate DNA amplification for single nucleotide mutation detection with ultrahigh sensitivity and selectivity.